A debate on the subject "Are SIRS and MODS important entities in the clinical evaluation of patients?" The con position - Baue, A E (Shock (Augusta, Ga.), 2000)
SIRS, MODS, and MOF are not diseases or even syndromes. They are simply clinical descriptors of people that are sick. They are symptoms and signs of various stages of illness progressing to death in the modern organ supporting ICU. They are catchy, popular acronyms but they cannot be treated specifically, and then only by support of organ functions. To help our patients and improve morbidity and mortality we must focus on specific diseases. Although ventilator associated pneumonia and pancreatitis may both produce an inflammatory response, cytokine-mediator activation and SIRS, they must each be treated in a different way. I believe that SIRS has led us astray.